Discovery of the genus Ancystrocerus Raffray in China, with description of a new species (Coleoptera: Staphylinidae: Pselaphinae) - Yin, Zi-Wei; Wang, Dan; Li, Li-Zhen (Zootaxa, 2015)
The tmesiphorine genus Ancystrocerus Raffray, 1893 is newly recorded in China, and a new species, A. chinensis Yin, Wang & Li sp. n., is described, figured, and compared with its congeners. New collection data of a previously described species Tmesiphodimerus sinensis Yin & Li is given.